Instant Coffee Cube / Ahmad Raziq Ab Hisham - Ahmad Raziq, Ab Hisham (2020)
The Cubesbrew.co is established on 20th January 2020. Our company is a manufacturer company which consist 1 member. The premise is located at Jalan Jasmine 4, Bukit Beruntung , 48300 Rawang, Selangor. The location selection is a strategic as it is near to the location of the raw materials and also to supply the product to the customers. We get the raw materials from Bean Shipper and Super Food Technology Sdn Bhd and innovate the coffee bean into a cube form instead of powdered formed. The target customer of our company is mostly hotels and supermarket. The operation hour are from 8 a.m. to 5 p.m. This company is in form individual. All position is appointed to one person only. The management team is led by the General Manager and assisted by other managers. Administration, Marketing, Operation and Financial manager work together to ensure that the company are properly managed.